2023
DOI: 10.1111/papt.12503
|View full text |Cite
|
Sign up to set email alerts
|

Pathways from childhood trauma to aberrant salience: A structural equation approach to mentalization model

Ercan Ozdemir,
Angus MacBeth,
Helen Griffiths

Abstract: ObjectiveThe aim of this study was to explore the relationship between affective disturbances and aberrant salience in the context of childhood trauma, attachment, and mentalization in an analogue study.MethodsUsing a cross‐sectional design, an online community sample completed self‐report measures of key variables. Structural equation modelling was used to test childhood trauma's influence on aberrant salience via a set of intermediate risk factors (depression, negative schizotypy, and insecure attachment). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
0
0
Order By: Relevance
“…For example, one recent study found that higher levels of schizotypy were significantly associated with the transition to a psychotic disorder from a clinical high-risk state, with negative schizotypy being the strongest predictor [67]. Another study found that negative schizotypy predicted increased aberrant salience in men but not women [68]. Taken together, the connections between negative schizotypy and the transition to a psychotic disorder and negative schizotypy and metacognitive deficits may elucidate the possibility that metacognitive interventions delay or prevent the transition to a schizophrenia spectrum or other psychotic disorder.…”
Section: Metacognition In Schizotypymentioning
confidence: 99%
“…For example, one recent study found that higher levels of schizotypy were significantly associated with the transition to a psychotic disorder from a clinical high-risk state, with negative schizotypy being the strongest predictor [67]. Another study found that negative schizotypy predicted increased aberrant salience in men but not women [68]. Taken together, the connections between negative schizotypy and the transition to a psychotic disorder and negative schizotypy and metacognitive deficits may elucidate the possibility that metacognitive interventions delay or prevent the transition to a schizophrenia spectrum or other psychotic disorder.…”
Section: Metacognition In Schizotypymentioning
confidence: 99%